Complications and outcomes of pregnancy in patients with antiphospholipid antibodies during various treatment methods - Yu. S. Bagdasarova; M. S. Zainulina; M. G. Nikolaeva (IRBIS LLC, 2023)
Introduction. Antiphospholipid antibodies (APAs) exert multifaceted effects on the course of pregnancy by disrupting microcirculation, affecting the hemostasis, as well as damaging the endothelial membranes, leading to early reproductive loss and development of placenta-associated complications depending on the affected gestation stage. Planning and management of pregnancy in women in the absence of criteria for complete antiphospholipid syndrome (APS) currently remains unresolved issue. The absence of generally accepted treatment standards for this category of patients and inability to substantiate the diagnosis according to the APS classification criteria complicate selection of therapeutic tactics.Aim: to conduct a comparative analysis of therapy-based complications and outcomes of pregnancy in APA carriers.Materials and Methods. During the period 2019-2021 a prospective study of 150 patients who entered pregnancy with aggravated obstetric and gynecological history, serum APA level was examined. Considering the risks of developing obstetric and thrombotic complications, all patients were prescribed prophylactic doses of low molecular weight heparins (LMWHs) and low doses of acetylsalicylic acid (ASA). The patients were divided into 3 groups using a random number generator. Group 1 (n = 50), in addition to the prescribed LMWH (enoxaparin sodium 40 mg 1 time per day) and ASA (150 mg 1 time per day), also underwent plasmapheresis (PF) 4 sessions per 1 course in 6-8, 12-14 and 22-24 weeks of pregnancy; group 2 (n = 50) received courses of intravenous immunoglobulins (IVIG) at a course dose of 300 ml (15 g) simultaneously; group 3 (n = 50) received no additional therapies. Rate of pregnancy complications was comparatively assessed - development of fetal growth retardation (FGR), low birth weight fetus, gestational arterial hypertension (AH), moderate and severe preeclampsia (PE), anemia and delivery outcomes.Results. It was found that in group 3 there was a higher incidence of gestational hypertension (p2,3 < 0.0001), moderate PE (p 1,3 =0.071; p 2,3 = 0.0019), low weight fetus for gestational age (p2,3 = 0.0002) and FGR (p2,3 = 0.003). In group 1, compared with group 2, there were more often observed small weight for gestational age fetus (p1,2 = 0.018) and FGR (p1,2 = 0.024), gestational hypertension (p1,2 = 0.0008), anemia (p1,2 < 0.0001) and latent iron deficiency (p1,2 < 0.0001). Also, groups 2 and 3 vs. group 1 were more likely to have intrahepatic cholestasis during pregnancy (p1,2 = 0.013; p1,3 = 0.003).Conclusion. In the group of patients receiving complex therapy consisting of LMWHs prophylactic doses, low ASA doses and IVIG courses, the risks of developing placenta-associated complications and iron deficiency were reduced compared to other groups indicating about a higher efficiency of this therapy regimen. However, the development of intrahepatic cholestasis during pregnancy was less common in the group of patients receiving PF courses, in contrast to using IVIG courses, which can be accounted for by additional effect of efferent therapeutic methods and should be taken into account in a differentiated approach for management of patients with liver and gallbladder pathology.